Hyperhomocysteinemia Is a Predictor for Poor Postoperative Angiogenesis in Adult Patients With Moyamoya Disease - He, Qiheng; Ge, Peicong; Ye, Xun; Liu, Xingju; Wang, Jia; Wang, Rong; Zhang, Yan; Zhang, Dong; Zhao, Jizong (Frontiers in Neurology, 2022)
Background and purposes: The risk factors of postoperative angiogenesis in moyamoya disease (MMD) patients remain unknown. We aimed to investigate the association between HHcy and postoperative angiogenesis of adult patients with MMD. Methods: A total of 138 adult patients with MMD were prospectively recruited from July 1 to December 31, 2019. After excluding 10 patients accepting conservative therapy and 77 individuals without postoperative digital subtraction angiography (DSA), all 51 MMD patients were enrolled, and 28 patients received bilateral operations separately. Patients were grouped according to postoperative angiogenesis and hyperhomocysteinemia (HHcy) presentation, respectively. Clinical data and laboratory examinations were compared. Potential risk factors were evaluated by univariate and multivariate logistic regression analysis. Nomogram was further performed. The biological functions of Hcy were explored in vitro. Results: Comparing to the normal, patients with poor postoperative angiogenesis were higher in serum Hcy (P=0.004), HHcy ratio (P=0.011), Cr (P<0.001), UA (P=0.036), Triglyceride (P=0.001), HDL-C (P=0.001), LDL-C (P=0.009), ApoA(P=0.022), ApoB(P=0.013). Furthermore, HHcy was more common in males (P = 0.003) than females. Logistic analysis results showed that Hcy (OR 0.817, 95%CI 0.707-0.944, P=0.006) was an independent risk factor. HHcy and creatinine were significantly associated with poor postoperative angiogenesis in MMD patients. Further, Hcy could inhibit the proliferation, migration, and tube formation of HBMECs, which can be reversed by VEGF. Conclusions: HHcy was significantly correlated with postoperative angiogenesis in adult patients with MMD. Hcy significantly inhibits HBMECs proliferation, migration, and tube formation. Furthermore, VEGF could reverse the inhibition effect induced by Hcy. Focusing on the pathophysiology and mechanism of HHcy might help to guide postoperative clinical management.